Islamic Thought Progressive Radical Reform: an Analytical Study of Tariq Ramadan's Concept of Ijtihad - Dzulkarnaen, Ahmad; Fathiyaturrahmah,; Haris, Abdul (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This research aims to analyze the concept of ijtihad renewal using Radical Reform initiated by Tariq Ramadan, by focusing on ijtihad as a topic of study to develop Islamic law. In the research, the research is based on qualitative methods with the type of literature review, as well as descriptive and historical content analysis of relevant sources. The results of this study are that the concept proposed in an organized manner by Ramadan is an appropriate step in the development of Islamic law, the demand for the birth of contemporary fiqh requires a critical and rational reading of the text through the ijtihad approach. However, while this spirit of reform is relevant, there are strict conditions that must be met to conduct ijtihad, both in terms of the qualifications of the mujtahid and other conditions. This is important to ensure that the resulting law is following the correct provisions of the Shari'ah.